Hubungan Pengetahuan dan Sikap Remaja Mengenai Gizi Seimbang dengan Status Gizi pada Masa Pandemi Covid-19 - Desak Made Malini; Tia Setiawati; Kartiawati Alipn; Nurullia Fitriani (Malahayati Nursing Journal, 2023)
ABSTRACT Maintaining a balanced nutritional intake is crucial to attaining the ideal nutritional status and optimal growth and development in adolescents. COVID-19 pandemic is also a driving factor for maintaining nutritional status as it will preserve the body's immune system in combating viral infections. Knowledge and attitudes related to balanced nutrition are one of the contributing factors to encourage adolescents to maintain their nutritional status. This study aimed to determine the relationship between the level of knowledge and attitudes related to balanced nutrition on nutritional status in adolescents aged 17-20 years. The research design used was a cross-sectional approach and the data were analyzed by the Chi-square test (α = 0.05). The results showed that there was no significant relationship between the level of knowledge and attitudes related to animal protein, fiber and vitamins, micro and macro minerals, general guidelines for balanced nutrition, and the four pillars of balanced nutrition on nutritional status (α 0.05). It can be concluded that the level of knowledge and attitudes of adolescents does not directly influence the nutritional status of adolescents aged 17-20 years during the COVID-19 pandemic. Keywords: Adolescents Attitude, Adolescents Knowledge, COVID-19, Nutritional Status  ABSTRAK Menjaga asupan gizi yang seimbang merupakan hal yang krusial untuk memiliki status gizi yang ideal dan untuk mencapai pertumbuhan dan perkembangan remaja yang optimal. Kondisi pandemi COVID-19 menjadi faktor pendorong untuk tetap mempertahankan status gizi karena dapat menjaga sistem imunitas tubuh dalam melawan infeksi virus. Pengetahuan dan sikap terkait gizi menjadi salah satu faktor yang berkontribusi untuk mendorong remaja dalam menjaga status gizinya. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat pengetahuan dan sikap terkait gizi seimbang dengan status gizi pada remaja berusia 17-20 tahun. Metode penelitian yang digunakan adalah pendekatan cross-sectional dan data dianalisis dengan uji Chi-square (α = 0,05). Hasil penelitian menunjukkan tidak ada hubungan yang signifikan antara tingkat pengetahuan dan sikap terkait protein hewani, serat dan vitamin, mikro dan makro mineral, pedoman umum gizi seimbang, dan empat pilar gizi seimbang dengan status gizi (α0,05). Hal ini dapat disimpulkan bahwa tingkat pengetahuan dan sikap remaja tidak memberikan pengaruh secara langsung dengan status gizi remaja berusia 17-20 tahun di masa pandemi COVID-19. Kata Kunci: COVID-19, Sikap Remaja, Status Gizi, Tingkat Pengetahuan Remaja